2023
DOI: 10.1073/pnas.2302584120
|View full text |Cite
|
Sign up to set email alerts
|

The SHDRA syndrome-associated gene TMEM260 encodes a protein-specific O-mannosyltransferase

Abstract: Mutations in the TMEM260 gene cause structural heart defects and renal anomalies syndrome, but the function of the encoded protein remains unknown. We previously reported wide occurrence of O-mannose glycans on extracellular immunoglobulin, plexin, transcription factor (IPT) domains found in the hepatocyte growth factor receptor (cMET), macrophage-stimulating protein receptor (RON), and plexin receptors, and further demonstrated that two known protein O-mannosylation systems orchestrate… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
30
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(36 citation statements)
references
References 62 publications
6
30
0
Order By: Relevance
“…We first aimed to improve these three key steps in our established workflow (13,17) for identification and quantification of O-Man proteins and establish an optimized workflow for O-Man glycoproteomics. Previous glycoproteomics studies have demonstrated that the majority (72%) of proteins undergoing O-Man glycosylation consists of single-pass or multi-pass transmembrane proteins (13,(17)(18)(19)35) (Fig. S1A).…”
Section: An Optimized Workflow For O-man Glycoproteomicsmentioning
confidence: 96%
See 4 more Smart Citations
“…We first aimed to improve these three key steps in our established workflow (13,17) for identification and quantification of O-Man proteins and establish an optimized workflow for O-Man glycoproteomics. Previous glycoproteomics studies have demonstrated that the majority (72%) of proteins undergoing O-Man glycosylation consists of single-pass or multi-pass transmembrane proteins (13,(17)(18)(19)35) (Fig. S1A).…”
Section: An Optimized Workflow For O-man Glycoproteomicsmentioning
confidence: 96%
“…HCD/ETciD-based bottom-up analyses identified 3882 glyco-PSMs from 120 unique O-Man proteins (Fig. 2A), 33 of which have not been described as O-Man substrates before (13,(17)(18)(19)35).…”
Section: An Expanded O-man Glycoproteome In Five Human Cells Linesmentioning
confidence: 99%
See 3 more Smart Citations